Application of Resveratrol in Diabetes: Rationale, Strategies and Challenges - Bagul, P.K.; Banerjee, S.K. (Current Molecular Medicine, 2015)
The increasing prevalence, involvement of several signaling pathways, variable pathogenesis, progressive natural history and complications of type 2 diabetes emphasize an urgent need for a molecule with multiple actions. Resveratrol (3,5,4'-trihydroxy-trans-stilbene) is a polyphenolic antioxidant present in red wine gaining a worldwide interest because of its multi-target effect against diabetes and other life-threatening diseases. Improving insulin sensitivity, enhancing GLUT4 translocation, reducing oxidative stress, regulating carbohydrate metabolizing enzymes, activating SIRT1 and AMPK, and decreasing adipogenic genes are some promising mechanisms established until now for resveratrol. Apart from these, resveratrol attenuates the end organ damage and reduced diabetic complications. Resveratrol exerts its beneficial antidiabetic action as evidenced from the in vitro, preclinical and clinical studies. Considering all the benefits of resveratrol in diabetes, resveratrol based different nutraceutical products have been developed commercially to use in humans. However, this compound is still under investigation because of some limitations. Resveratrol can be taken in to account in the treatment of diabetes after overcoming all hurdles and difficulties. This article examines the basic scientific evidences, animal experiments, and human/clinical data supporting the antidiabetic action of resveratrol and describes the strategies and challenges to recommend resveratrol from preclinical to clinical use.
Keywords: diabetes